HEDGES: THE EXPRESSIONS OF DOUBT AND CERTAINTY - Sri Mulatsih (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
Hedges are linguistic resources which convey the fundamental characteristics of science of doubt and certainty. Hedges are mostly verbal and adverbial expression such as could, perhaps,may, suggest which deal with degrees of probability. Hedges can be considered as the interactive elements which serve as a bridge between the propositional information in the text and the writerâ€™s factual interpretation. Based on Meyer in Miller (1994: 109-110) hedges are expressed in the following strategic stereotypes: modal auxiliary verbs; modal lexical verbs of varying degree of illocutionary force; adjectival, adverbial, and nominal modal phrases; approximators of degree, quantity, frequency, and time; introductory phrases; if clauses; and compound hedges. While the reasons why people use hedges are minimizing the â€œthread-to-faceâ€, being a way of being more precise in reporting results, being positive or negative politeness strategies, and conforming to an established writing style.Keywords: hedges, taxonomy, style of writing, politeness strategies,strategic stereotypes.